Introduction to research methods and data analysis in psychology - Langdridge, Darren., & Hagger-Johnson, Gareth; Hagger-Johnson, Gareth (b)
This third edition of Introduction to Research Methods and Data Analysis in Psychology provides you with a unique, balanced blend of quantitative and qualitative research methods. Highly practical in nature, the book guides you, step-by-step, through the research process and is underpinned by SPSS screenshots, diagrams and examples throughout.
Includes references and index.
Keywords: Introduction to research methods